Sistem Pendukung Keputusan Dalam Rekomendasi Kelayakan Nasabah Penerima Kredit Menerapkan Metode Multi Object Optimization on the Basis of Ratio Analysis (MOORA) - Aprilia Cahyani, Regyn; Lingga Wijaya, Harma Oktavia; Hakim, Lukman (STMIK Budi Darma, 2024)
The process of applying for credit (loan funds) by customers is one of the many forms of service at the bank. To approve a credit application, the bank, especially the credit manager, must carry out a complex assessment in accordance with the standard requirements that apply in the bank, this is because to minimize the risk of bad credit because the customer cannot make installment payments in the future. Due to the complexity of considerations in determining the eligibility of customers applying for credit, limited employees (labor) and also the assessment process that is still carried out manually so that it takes a long time, so to overcome these problems, a system is needed that can provide recommendations for customer decisions that are worthy of acceptance in applying for credit. By using one of the methods in the decision support system, it is hoped that the credit application process can run faster. One of the methods in SPK is the Multi Object Optimization on the Basis of Ratio Analysis (MOORA) Method. The criteria used in this assessment process include collateral, income, completeness of files, financial statements and mandatory net data from loans. Based on the results of the calculation according to the predetermined criteria, the highest score is obtained on behalf of the name with a value of 0.4591 0.59 and the lowest is held by Rahma with a value of 0.2172